2004
DOI: 10.1007/bf03040900
|View full text |Cite
|
Sign up to set email alerts
|

Human albumin and starch administration in critically ill patients: A prospective randomized clinical trial

Abstract: Raising colloid osmotic pressure with human albumin in hypoalbuminemic patients is not associated with improvement of the clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 20 publications
0
49
0
1
Order By: Relevance
“…In elderly patients after cardiac surgery, there was no difference in renal dysfunction between the group with albumin supplementation and the group given 6% hydroxyethyl starch (HES) instead of albumin; moreover, endothelial activation was even lower in the HES group [25]. In ICU patients, albumin replacement increased colloid osmotic pressure, but it did not improve fluid balance and pulmonary edema [26], nor did it reduce mortality, duration of ICU stay, mechanical ventilation, or renal replacement therapy [27].…”
Section: Discussionmentioning
confidence: 93%
“…In elderly patients after cardiac surgery, there was no difference in renal dysfunction between the group with albumin supplementation and the group given 6% hydroxyethyl starch (HES) instead of albumin; moreover, endothelial activation was even lower in the HES group [25]. In ICU patients, albumin replacement increased colloid osmotic pressure, but it did not improve fluid balance and pulmonary edema [26], nor did it reduce mortality, duration of ICU stay, mechanical ventilation, or renal replacement therapy [27].…”
Section: Discussionmentioning
confidence: 93%
“…Hypoalbuminemia is a common finding in septic patients and is associated with higher morbidity and mortality rates (20). However, the use of albumin to treat hypoalbuminemia in intensive care unit patients remains controversial, with some studies suggesting improved outcomes with correction of hypoalbuminemia (21) and others suggesting no benefit (22,23). The large, multicenter, prospective, randomized controlled trial, the saline versus albumin for fluid resuscitation in the critically ill study (24), suggested that albumin administration may improve outcome in the subgroup of patients with sepsis, although the differences did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of hypoalbuminemia with hyperoncotic albumin to raise the colloidal oncotic pressure in critically ill patients has been shown not to improve outcome. 6 This is because the underlying pathogenesis of hypoalbuminemia in critical illness is increased capillary permeability due to systemic inflammatory response syndrome leading to interstitial edema and organ failure or dysfunction. Because 60% of albumin is normally in the interstitial space and 6 g/h move from the vascular to interstitial space in a normal person, it is not an ideal volume expander in the sick hypoalbuminemic patient in whom capillary permeability is much increased.…”
mentioning
confidence: 99%